WHO Melting-Point Reference Substances - Bervenmark, H. (1963)
Batches of 13 highly purified chemicals, intended for use as reference substances in the calibration of apparatus for melting-point determinations, have been subjected to a collaborative assay by 15 laboratories in 13 countries. All the laboratories performed melting-point determinations by the capillary methods described in the proposed text for the second edition of the Pharmacopoea Internationalis and some, in addition, carried out determinations by the microscope hot stage (Kofler) method, using both the “going-through” and the “equilibrium” technique. Statistical analysis of the data obtained by the capillary method showed that the within-laboratory variation was small and that the between-laboratory variation, though constituting the greatest part of the whole variance, was not such as to warrant the exclusion of any laboratory from the evaluation of the results. The average values of the melting-points obtained by the laboratories can therefore be used as constants for the substances in question, which have accordingly been established as WHO Melting-Point Reference Substances and included in the WHO collection of authentic chemical substances. As to the microscope hot stage method, analysis of the results indicated that the values obtained by the “going-through” technique did not differ significantly from those obtained by the capillary method, but the values obtained by the “equilibrium” technique were mostly significantly lower.